Implementasi Program Adiwiyata Mandiri untuk Meningkatkan Karakter Peduli Lingkungan Siswa di Sekolah Dasar - Maulidah, Widya Dewi; Wahyuni, Akhtim (MODELING: Jurnal Program Studi PGMI, 2023)
This research aims to describe the Implementation of Adiwiyata Program in Elementary School. There are 2 focus problems, namely; (1) How is the implementation of the Adiwiyata Mandiri Program in improving students' environmental care character in elementary schools? (2) What are the obstacles in the implementation of the implementation of the Adiwiyata Mandiri Program in improving students' environmental care character in elementary schools? The type of research conducted is descriptive qualitative. Data collection techniques were conducted by interview, questionnaire, observation and documentation. The results obtained related to the implementation are generally implemented through four aspects, including aspects of environmentally sound policies, environmentally-based school curriculum, participatory-based activities and management of environmentally friendly supporting facilities. Students managed to implement the Adiwiyata Program independently based on each indicator of environmental care character. The obstacles faced include a non-uniform understanding of the objectives of the Adiwiyata Program and the lack of participation of some students in protecting the environment as a program to care for nature and themselves.